New approach for building multidisciplinary teams: case of surgical teams. (1st January 2013) - Khatrouch, Ikram; Kaddes, Mourad; Kermad, Lyes; Boujelbene, Younes; ElMhamedi, Abderrahman
One of the problems in human resources management in healthcare systems is the scouting or building of new team members to enhance the quality of healthcare. This paper proposes a new general model for multidisciplinary team building. The proposed model takes professional's preferences into account when a team building process is required for any type of project. We test the effectiveness of the model using medical domains of different complexities and describe some practical experiences of using the model in the surgical team building process.